Nano-biofertilizers for sustainable agriculture development under changing climatic conditions - Kumawat, Kailash Chand; Kumar, Ajay (Indian Farming, 2022)
Precise nutrient management of crops, soil fertility and soil health will be a major challenge worldwide in the future because intensive cropping systems rely predominantly on diverse types of agro-chemicals. The use of conventional or synthetic agro-chemicals suffers from lower nutrient use efficiency, negative impact on the environment and soil health, and higher loss of water bodies. Nano-biotechnology is a promising alternative biological strategy having the potential to revolutionize agricultural systems by delivering nutrients to crops in a controlled release manner. Engineering nano-particle based nano-fertilizers offer benefits in crop nutrition management by enhancing abiotic stress tolerance such as salinity, drought as well as high temperature and improve agricultural productivity in a sustainable way. This article focusses on the role of macronutrient, micronutrient-based nano-fertilizer as well as nano-biofertilizer towards the development of smart and sustainable future agriculture.